Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.3649
|View full text |Cite
|
Sign up to set email alerts
|

THU0019 Features of telomere length distribution on individual chromosomes in rheumatoid arthritis

Abstract: BackgroundTelomeres are nucleoprotein structures,that protect the ends of chromosomes during cell divisions [1,2,3]. Previously it was found, that average telomere length in immune cells is reduced in atopic and autoimmunity disorders.This fact indicates an early immune aging in immune-mediated diseases [4,5]. The distribution of telomere repeats on different chromosomes has an individual telomere profile in humans [6] and may be a congenital feature, that accelerates immunosenescence.ObjectivesThe purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since occupational balance and stress are related (10,37), it was expected that occupational balance would be associated with TL via the stress pathway (38). However, occupational balance was not significantly associated with TL in this sample; nor did TL differ between groups, which was also unexpected given prior research showing shorter telomeres in patients with arthritis (21,39,40). Research has shown stress as a pathway through which lifestyle influences telomere biology.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Since occupational balance and stress are related (10,37), it was expected that occupational balance would be associated with TL via the stress pathway (38). However, occupational balance was not significantly associated with TL in this sample; nor did TL differ between groups, which was also unexpected given prior research showing shorter telomeres in patients with arthritis (21,39,40). Research has shown stress as a pathway through which lifestyle influences telomere biology.…”
Section: Discussionmentioning
confidence: 53%
“…However, the different factors and mechanisms that influence TL are still largely unknown (43). The absence of associations between occupational balance and TL, and MCS score and TL, may be sample specific given that the present sample did not replicate the between-group difference in TL found in other studies (21,39,40). The mechanism through which occupational balance and TL may be associated is complex and requires replication before concluding that there is no relationship.…”
Section: Discussionmentioning
confidence: 66%